Cyprus at war diplomacy and conflict during the 1974 crisis - Asmussen, Jan (Library of international relations ;, 2008)
Based on the records from the British and American governments, this book explores why both the British and the Americans decided not to inform the Cyprus government as well as the reasons behind Britain's surprising reluctance to exercise her right of intervention on the island. It analyses the background to the 1974 war.